Kajian perbaikan mutu pada agroindustri skala mikro dan kecil gambir indonesia - Endang Gumbira Said; Khaswar Syamsu; A. Herryandie; E. Mardliyati; N. A. Evalia (Institut Pertanian Bogor, 2010)
Quality is an absolute requirement used by product to compete in the global market. Therefore, as the competition is getting more tight , high-quality gambier products become an absolute demands that must be met. One of the steps that must be taken is continuous technological improvement. In this study, quality analysis of various raw gambier samples of Lima Puluh Kota regency and the Padang City in West Sumatera, and Musi Banyu Asin regency in South Sumatra was done. The results of dimensional measurement and weighing samples of Bootch Gambier, Lumpang Gambier, Wafer Block and Stick Gambier showed that the quality of raw gambier were very various. The variation occured because the drying process and storage of gambier were not good enough. The proximate analysis data showed, in terms of ash content, only two types of Gambier samples (Bootch CVR Gambier and Wafer Block CVR Gambier) that met quality requirements, whereas the Coin Gambier and Bootch CVA Gambier had a very high ash content (38.93 percent and 75.64 percent).